1984
DOI: 10.1192/bjp.144.2.149
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Dangerousness Assessments. A Decision Making Exercise

Abstract: One hundred and ninety three raters drawn from six countries and representing different professional groups considered 16 case histories. Raters were asked to indicate what degree of 'dangerousness' they attributed to each individual and what they considered to be the optimal management. The level of agreement between raters concerning the assessment of dangerousness was generally low, the level of 60 per cent being reached for only 4 cases out of 16. Psychiatrists did not reach a higher level of agreement on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…For example, Montandon and Harding asked 193 raters to assess thè dangerousness' of 16 individual s on a four-point scale ranging from 0 (no dangerousne ss) to 3 (extreme dangerousne ss). 6 The case reports used in their study comprised individual s who were: 1. both violent and mentally ill (n=4); 2. violent but not mentally ill (n=4); 3. not violent but mentally ill (n=5); and 4. neither violent nor mentally ill (n=3). The level of agreement between the raters was generall y found to be quite poor (range 29 ± 86%), with a level of 60% being reached in only one quarter of cases; at worst, agreement only marginally exceeded chance levels (29% vs. 25%).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Montandon and Harding asked 193 raters to assess thè dangerousness' of 16 individual s on a four-point scale ranging from 0 (no dangerousne ss) to 3 (extreme dangerousne ss). 6 The case reports used in their study comprised individual s who were: 1. both violent and mentally ill (n=4); 2. violent but not mentally ill (n=4); 3. not violent but mentally ill (n=5); and 4. neither violent nor mentally ill (n=3). The level of agreement between the raters was generall y found to be quite poor (range 29 ± 86%), with a level of 60% being reached in only one quarter of cases; at worst, agreement only marginally exceeded chance levels (29% vs. 25%).…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of the professional background of the rater, the level of pair-wise rater agreement was only moderate and, in some cases, rather poor.Moreover, in a later study (Gale et al, 2003), we found that mental health professionals had profound difficulties with some simple arithmetic and probabilistic concepts that underlie risk measurement. These studies, amongst others (e.g., Montandon & Harding, 1984;Harriss & Hawton, 2005) raise important questions about the reliability and validity of risk assessment in current mental health practice.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, legislation and guidelines in the mid-1990s in the UK reinforced the importance of thorough risk assessment and management (DoH, 1994;1995;HMSO, 1995). Previous studies on the risk assessment of psychiatric patients has highlighted inter-professional variability in the levels of risk ascribed to specific cases (Montandon & Harding, 1984;Ryan, 1998). The gender of the assessor is also known to be a significant factor in determining whether ratings are more or less cautious (Ryan, 1998;Gale et al, 2002).…”
Section: Introductionmentioning
confidence: 99%